The challenge of conserving indigenous domesticated animals - Mendelsohn, R. (Elsevier, 2003)
This special issue contains many valuable studies of indigenous domesticated animal genetic resources. Individual farmers throughout the world are abandoning many breeds that have been locally adapted over thousands of years in favor of new exotic but more productive breeds. Economics can explain some of this transition as cheaper grains and modem genetic tools have made more intensive husbandry more profitable. Poorly designed government policies may have contributed to the decline as well. The general decline of indigenous species especially in developing countries raises many conservation issues. What role should local breeds continue to have in local economies? Is there a social argument such as keeping historical livelihoods intact or keeping genetic diversity intact for government programs to maintain economically inferior breeds? What is the most efficient design for animal conservation programs?